Experimental Investigation of a Convection - Improved Solar Salt Evaporation System - Nizar Amir,; Makhfud Efendy,; Mohd Nazri Latiff Azmi, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The need for salt in Indonesia has recently intensified, as evidenced by the increasing salt demand in various sectors, including consumption, industry, and pharmaceuticals. However, this need has not been fulfilled optimally because of the dependence of salt production on natural weather. Thus, the development of enhanced evaporation technologies to improve evaporation rates has gained much attention. This study aimed to use proposed technology to enhance salt production by evaporating seawater. This method was used to accelerate the evaporation rate of brine by increasing its specific gravity before it entered a crystallization pond. An experimental investigation was carried out to determine the evaporation rate of the system. The results showed that this system can improve the evaporation rate by 11 times compared to conventional methods. The highest accumulated evaporation rate that could be achieved was 34.85 L/m2/day, while the lowest accumulated evaporation rate was found to be 23.6 L/m2/day. Using the proposed system, the time required to enhance the brine specific gravity from 1,030 kg/m3 to 1,208 kg/m3 can be reduced from 30 days to 15 days. This study revealed that using a convection-improved solar salt evaporation system can enhance brine evaporation and reducing the current time consumption and land requirements of saltworks.